1998
DOI: 10.1109/75.704410
|View full text |Cite
|
Sign up to set email alerts
|

Performance of low-loss RF MEMS capacitive switches

Abstract: This letter details the construction and performance of metal membrane radio frequency MEMS switches at microwave and millimeter-wave frequencies. These shunt switches possess a movable metal membrane which pulls down onto a metal/dielectric sandwich to form a capacitive switch. These switches exhibit low loss (< < <0.25 dB at 35 GHz) with good isolation (35 dB at 35 GHz). These devices possess on-off capacitance ratios in the range of 80-110 with a cutoff frequency (figure of merit) in excess of 9000 GHz, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
160
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(164 citation statements)
references
References 6 publications
0
160
0
4
Order By: Relevance
“…2. The switch could be the standard capacitive shunt design developed by Raytheon with a center pull-down electrode [2], or the DC-contact shunt switch with two pull-down electrodes developed by Muldavin et al [12], and Feng et al [13]. Alternatively, it could also be a low spring-constant switch (Pacheco et al [4]).…”
Section: Brownian Noise Effects For Mems Shunt Switchesmentioning
confidence: 99%
See 2 more Smart Citations
“…2. The switch could be the standard capacitive shunt design developed by Raytheon with a center pull-down electrode [2], or the DC-contact shunt switch with two pull-down electrodes developed by Muldavin et al [12], and Feng et al [13]. Alternatively, it could also be a low spring-constant switch (Pacheco et al [4]).…”
Section: Brownian Noise Effects For Mems Shunt Switchesmentioning
confidence: 99%
“…(2,4) are used, the phase noise relative to the carrier due to the reflection from the MEMS series switch becomes:…”
Section: Brownian Noise In Mems Series Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [6] because the signal lines are also part of the electrostatic actuator. It has also been found that a metal-to-insulator mechanical contact can be more reliable than a metal-to-metal contact and hence switches are made that are variable capacitors.…”
Section: Series Switchmentioning
confidence: 99%
“…Over that time MEMS devices have become a focus for research in microwave switches [4][5][6]. For a review of RF MEMS devices see [7].…”
Section: Introductionmentioning
confidence: 99%